#UsToo: implicit bias, meritocracy and the plight of black minority leaders in healthcare. Issue 4 (11th October 2019) - Busari, Jamiu O
Abstract : In the fall of 2017, the #MeToo movement ushered in one of the most astonishing revolts against the perils of workplace-related harassment. Several unsuccessful campaigns geared towards ending the harassment and subjugation of women in corporate organisations finally got a thrust that resulted in significant and far-reaching changes in many organisations. While the #MeToo movement highlighted the pains and struggles of gender inequality over the years, an unintended consequence has been the shadow it has cast over the plight of other minority groups facing harassment in the workplace. In several academic and healthcare (learning) environments, people of colour, like women, face explicit and implicit forms of harassment on a regular, if not daily basis. Unlike gender harassment, however, racial harassment affects both sexes with relatively more predominance among men. The effect of racial harassments does not just impact performance and self-confidence but also influences the opportunities available to black professionals to advance their academic and professional careers. In the academic and healthcare industries, the issue of how to tackle implicit bias and unfair practices is not clear-cut. While the subjugated feel the impact of bias, the perpetrators of the actions either lack the ability (or are unwilling) to acknowledge these biases. Furthermore, the complexities inherent to the different contexts make it problematic if not impossible, to call out racist behaviours. In this paper, a real-life case scenario is used to provide a scholarly analysis of the dynamics of racial harassment, implicit bias and the impact on minority leader roles in healthcare delivery.